Legal policy of the Indonesia's natural disaster insurance system: A human rights perspective under the 1945 Constitution - Afkar, Kardiansyah; Mochtar, Zainal Arifin; Putri, Karina (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The role of the insurance sector in national economic growth has a very strong correlation and can be utilised for financing schemes for natural disaster management. This study aims to investigate whether insurance, national economic growth, and the utilisation of insurance for natural disaster management have a constitutional correlation with a constitutional law approach. This research is conducted using the doctrinal research method. The doctrinal research method is an analysis of positive law, related cases, and other relevant references in studying a legal issue. This study found that in the constitutional law system, the correlation between catastrophe insurance and national economic growth is closely related to the mandate of Article 33 of the 1945 Constitution, which states that the insurance service sector can be classified as an essential for the lives of many people, so that it must be structured based on the principle of kinship. Therefore, the legal policy of the insurance system in Indonesia must be structured based on the principles of economic democracy, togetherness, equitable efficiency, sustainability, environmental insight, independence, and maintaining a balance of progress and national economic unity. In more specific, the correlation between the utilization of insurance in natural disaster management can be linked to the Articles of Human Rights contained in the 1945 Constitution. So the legal policy of the insurance system, especially catastrophe insurance, should not only provide (economic) benefit for business actors but also involve a public service dimension for society.